IRE-1 regulates cellular homeostasis during disrupted lipid metabolism - Koh, Jhee Hong (Nanyang Technological University, 2021)
Metabolic disorders, such as non-alcoholic fatty liver disease (NAFLD), are emerging as epidemics that affect the global population. One facet of these disorders is attributed to the disturbance of membrane lipid composition. Typically activated by misfolded protein accumulation within the ER, perturbation of endoplasmic reticulum (ER) homeostasis through alteration in membrane phospholipids or change in membrane lipid saturation to unsaturation ratio also activate the unfolded protein response (UPR) and cause dramatic transcriptional and translational changes in the cell. To restore cellular homeostasis, the three highly conserved UPR transducers ATF6, IRE1, and PERK mediate adaptive responses to ER stress. Understanding the differences of how lipid dysregulation causes ER perturbation is critical, as it will provide insights into the pathophysiological mechanism of metabolic diseases. Furthermore, new insights into how proteotoxic stress differs from lipid bilayer stress (LBS) may also aid in specific targeting of the UPR for a better therapeutic outcome. Our goal in this project is to establish a model system in the nematode Caenorhabditis elegans to differentiate proteotoxic stress-induced UPR and LBS-induced UPR. We evaluated sources of stress that activate UPRLBS and identified three factors that warrant further studies. These factors are (1) increased lipid unsaturation through cold stress, (2) increased lipid saturation through glucotoxicity, and (3) phosphatidylcholine (PC) deficiency through silencing of the PC biosynthesis gene phosphatidylethanolamine N-methyltransferase 2 (pmt-2). They share the common theme where perturbed cellular homeostasis caused by these factors activate IRE-1 through LBS. We show that the worms are highly responsive to PC depletion and strongly activates the UPRLBS. Hence, we focused our understanding of the UPRLBS by utilizing the PC deficiency model. Transcriptional profiling of PC-deficient worms revealed a unique subset of genes regulated in a UPR-dependent manner that is independent of proteotoxic stress. Among these, we show that autophagy is modulated through the conserved IRE-1–XBP-1 axis, strongly suggesting of the importance of autophagy in maintaining cellular homeostasis during the LBS-induced UPR.